(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2022)
Studies have clearly shown that there are numerous health benefits accruing from breastfeeding, not only to infants but mothers also. However, adherence to breastfeeding practice remains a key challenge facing mothers and maternal health providers. The study which adopted survey research approach critically examined audience response to media campaign on the importance of breastfeeding in Arochukwu community of Abia State, Nigeria to determine the factors that actually militate against its practice as an ideal, healthy and accepted norm. Structured questionnaire was the principal instrument of data collection. A number of 185 respondents were randomly selected from seven health centers in the area, representing the population of the study. The data obtained were analyzed using tables and simple percentage calculation and graphs respectively to elucidate on the findings. Findings reveal that civilization/new cultural ideas were contributory to the decline in breastfeeding rate in Arochukwu. It was also found that there was a huge influence of the effects of social perception and lack of education resulting to mothers’ neglect of breastfeeding practice in the area. Hence, the study concludes that the media and stakeholders in the health sector need to do more to effectively make mothers appreciate and appropriate the invaluable benefits of breastfeeding practice. It further recommends that conscious efforts should always be made by media campaigners to appropriately select and utilize suitable media channels for effective realization of objectives; more so, in the present context of addressing this key challenge of non-adherence to breastfeeding practice facing mothers generally, and particularly young mothers. JEL Classification Codes: H51, H52, H53, H75